Preptin Deficiency Does Not Protect against High‐Fat Diet‐Induced Metabolic Dysfunction or Bone Loss in Mice - Emma J. Buckels; Joey Tan; Huai‐Ling Hsu; Yuting Zhu; Christina M. Buchanan; Brya G. Matthews; Kate L. Lee (JBMR Plus, 2023)
ABSTRACT Preptin is derived from the cleavage of the E‐peptide of pro‐insulin‐like growth factor (IGF)‐II and is an insulin secretagogue. Observational studies have linked elevated circulating preptin to metabolic dysfunction in humans; however, a causal role for preptin in metabolic dysfunction has not been established. Additionally, preptin can promote osteoblast proliferation and differentiation, suggesting a link with skeletal health. We previously described a global preptin knockout (KO) model. In this study, we sought to uncover the impact of preptin KO in mice on the response to a moderately high‐fat diet (HFD) and low‐fat diet (LFD). HFD groups had higher weight and fat mass gain, lower trabecular and cortical bone volume and fracture load, and higher liver triglycerides. In males, preptin deficiency led to lower blood glucose than wild‐type (WT) mice under LFD conditions. This was accompanied by differences in bone microarchitecture, including lower trabecular bone volume fraction, trabecular number, and lower cortical thickness. These differences were absent in female mice, although KO females had a HFD‐driven increase in fat mass and liver triglycerides that was absent in WT mice. Female WT mice had increased glucose‐stimulated insulin secretion under HFD conditions that was absent in female KO mice. Overall, preptin may have a detrimental impact on metabolism and a positive impact on bone health in male mice and may protect against liver fat storage in females while enabling islet compensation under HFD conditions. When we consider that serum preptin levels are elevated in humans of both sexes in pathological states in which insulin levels are elevated, the impact of preptin on comorbidity risk needs to be better understood. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.